Assessing per- and polyfluoroalkyl substances (PFAS) in sediments and fishes in a large, urbanized estuary and the potential human health implications - Pulster, Erin L.; Rullo, Kylee; Gilbert, Sherryl; Ash, Thomas M.; Goetting, Barbara; Campbell, Kevin; Markham, Sara; Murawski, Steven A. (Frontiers in Marine Science, 2022)
The primary source of chronic exposures to per- and polyfluoroalkyl substances (PFASs) in humans is through the ingestion of contaminated foods and drinking water, with fish and other seafood being a major contributor. Nevertheless, there is scant literature on the dietary exposure to PFASs for the general United States (U.S.) population. The Tampa Bay (Florida, USA) region has the highest population density in the State and communities and their attendant support services are arrayed in an urban to semi-rural continuum from the head of the Bay to the ocean mouth. Tampa Bay supports productive recreational and commercial fisheries, providing a diverse community of species. A variety of potential PFAS sources surround Tampa Bay including airports, industry, wastewater treatment plants, fire-fighting training areas and military installations. The objective of this study is to quantify PFASs in sediment and fishes collected from Tampa Bay to further estimate human health risks from dietary exposures. Sediment (n = 17) and fish (24 species, n = 140) were collected throughout Tampa Bay in 2020 and 2021 and analyzed for 25 PFAS compounds. Concentrations of PFASs in sediments and edible tissues of fish ranged from 36.8 to 2,990 ng kg-1 (dry weight) and 307 to 33,600 ng kg-1 (wet weight), respectively. Generally, levels were highest in Old Tampa Bay and decreased south towards the Gulf of Mexico. Profiles in both matrices were generally dominated by perfluorooctane sulfonic acid (PFOS) with variations by location. Estimated human health risks from the consumption of contaminated fish collected in Tampa Bay exceeded concentration thresholds for minimum risk levels (MRLs) and tolerable weekly intake (TWIs) values for adults and youths. Additionally, concentrations of PFOS in edible fish tissues of several recreationally important species collected in Tampa Bay exceeded consumption guideline levels established by several governmental agencies. In the current context, the elevated levels of PFAS in Tampa Bay and the exceedances of available thresholds for potential human health risks are a cause for concern and justify a more intensive examination especially for more heavily utilized species, particularly those used in subsistence-level fishing, which, as elsewhere may be significantly under documented.